Universal health coverage in the context of population ageing: What determines health insurance enrolment in rural Ghana? - Nele Van der Wielen; Andrew Amos Channon; Jane Falkingham (BMC, 2018)
Abstract Background Population ageing presents considerable challenges for the attainment of universal health coverage (UHC), especially in countries where such coverage is still in its infancy. Ghana presents an important case study on the effectiveness of policies aimed at achieving UHC in the context of population ageing in low and middle-income countries. It has witnessed a profound recent demographic transition, including a large increase in the number of older adults, which coincided with the development and implementation of a National Health Insurance Scheme (NHIS), designed to help achieve UHC. The objective of this paper is to examine the community, household and individual level determinants of NHIS enrolment among older adults aged 50-69 and 70 plus. The latter are exempt from NHIS premium payments. Methods Using the Ghanaian Living Standards Survey from 2012 to 2013, determinants of NHIS enrolment for individuals aged 50-69 and 70 plus living in rural Ghana are examined through the application of multilevel regression analysis. Results Previous studies have mainly focused on the enrolment of young and middle aged adults and considered mainly demographic and socio-economic factors. The novel inclusion of spatial barriers within this analysis demonstrates that levels of NHIS enrolment are determined in part by the community provision of healthcare facilities. In addition, the findings imply that insurance enrolment increases with household expenditure even for those aged 70 plus who are exempt from the NHIS premium payment. Conclusion Adequate and appropriate infrastructure as well as health insurance is vital to ensure movement to UHC in low and middle income countries. Overall, the results confirm that there remain significant inequalities in enrolment by expenditure quintile that future policy reform will need to address.